1983
DOI: 10.1164/arrd.1983.128.3.491
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance in Adults of Air-flow Obstruction, but not of Mucus Hypersecretion, to Mortality from Chronic Lung Disease

Abstract: From 1954 to 1961, pulmonary function was assessed in 2,718 British men by forced expiratory maneuvers, and mucus hypersecretion and smoking habits were assessed by questionnaires. In 20 to 25 yr of follow-up, 104 men (all of whom had smoked) died of chronic obstructive pulmonary disease (COPD). The risk of death from COPD was strongly correlated with the initial degree of air-flow obstruction. Among men with similar initial air-flow obstruction, however, age-specific COPD death rates were not significantly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
160
0
7

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(177 citation statements)
references
References 25 publications
9
160
0
7
Order By: Relevance
“…In 1983, PETO et al [8] described a 10-fold increase in risk of death from respiratory disease over the 20 subsequent years in those with a FEV1 more than two standard deviations below average. In developing these new classification criteria we have used z-scores as an essentially identical approach to help stratify severity of disease state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1983, PETO et al [8] described a 10-fold increase in risk of death from respiratory disease over the 20 subsequent years in those with a FEV1 more than two standard deviations below average. In developing these new classification criteria we have used z-scores as an essentially identical approach to help stratify severity of disease state.…”
Section: Discussionmentioning
confidence: 99%
“…The z-score (signifying the number of standard deviations a result is from the mean predicted value) provides a metric for achieving this. A similar approach has previously been shown to provide effective risk stratification for death from respiratory and vascular causes [8].…”
Section: Introductionmentioning
confidence: 95%
“…(12) 12 (17) 19 (3) 13 (5) 9 (2) Effects on decline in FEV1-Decline in FEV1 in 14 (20) 13 (2) 60 (24)*** 22 (5) continuously treated patients was -0-086 1/year and in study group with crossover treatment and three other patients treated on demand -0-029 1/year. 0-111 1/year) (p<0-05) (fig 2).…”
Section: Introductionmentioning
confidence: 99%
“…2 The hypothesis has been put forward that early continuous bronchodilator treatment of reversible airflow obstruction will improve their prognosis, 3 Patients were randomly allocated to use salbutamol during one year and ipratropium bromide during the other in a crossover design (Fig 1). The long term effects were expected to be less distinct with respect to the drug than to the treatment regimen, and the variation within patients was expected to be less than between patients.…”
Section: Introductionmentioning
confidence: 99%
“…4 Some years later, Richard Peto, Charles Fletcher and others also showed that mortality in a number of occupational cohorts was strongly associated with the 1-second forced expiratory volume (FEV 1 ) but that it was not associated with the presence of chronic mucus hypersecretion when the association with ventilatory function had been taken into account. 5 Not everyone has fully accepted the passing of the British hypothesis. In particular, it has been argued that the role of mucus is still important in the later stages of disease.…”
Section: The British Hypothesismentioning
confidence: 99%